A case study of the effectiveness of visual merchandizing design elements on the market appeal of a selected women's apparel store - Mora, Maria Angelica Mikaela G.; Mayo, Adelaida Villaraza (2008.)
This thesis is a case conducted to determine the effectiveness of visual merchandising elements utilized by a specific brand of women's apparel chain. Specifically the study sought to identify if there was a relationship between store design elements and customer attraction to the store, known as Brand K for purposes of confidentiality, which has several branches or outlets in the Philippines as well as outlets outside the country. Store design elements were translated into operational policies which the management of Brand K implemented in each of their stores. This study focused on three outlets located in Metro Manila, specifically in Quezon City, namely those located in SM North, Trinoma, and Gateway. The researcher utilized an observational checklist during the ocular inspection. A survey was also conducted among female students from the University of the Philippines Diliman with the ages of 16-24. The sampling used was purposive and the parameters used in the selection were the following: 1) the respondents had to be female 2) the respondents had to be at least 16 years of age and not more than 34. This was to ensure that they fell under the market segment that Brand K targets. The researcher used the retail theory or approach: Shopping as Theater as basis for the analysis of the data obtained from the survey. The results of the study suggest that store design elements did have a hand in attracting customers to enter the shop and browse through the merchandise. Results regarding purchasing were inconclusive. A significant implication of the study was the emergence of the concept of sensory retailing where the use of visual elements, colors, scents and taste were applied as visual merchandising strategies in the store.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Display of merchandise -- Philippines; Women's clothing -- Merchandising